The Effectiveness of YouTube-Based Folk Story Video Learning Media to Improve Learning Outcomes in Writing Drama Texts Among Grade XI Students of SMK EKATAMA Pekanbaru - Fitrah Fitrah; Charlina Charlina (Dinasti International Journal of Education Management And Social Science, 2025)
This study aims to examine the effectiveness of instructional media based on folk tale videos in improving students’ learning outcomes in drama script writing skills among 11th-grade students at SMA EKATAMA. Writing drama scripts is often a challenging task for students, as it requires an understanding of dramatic structure, character development, and a coherent and engaging plot. Engaging and contextual learning media are needed to help students overcome these difficulties. The research employed a quasi-experimental method with a quantitative approach. Data were collected through written tests administered before and after the treatment (pre-test and post-test), as well as through classroom observation. The results indicate that the use of YouTube-based folk tale videos significantly enhances students’ performance in writing drama scripts compared to conventional teaching methods.